Factors Affecting Emission Concentrations in Small Heat Sources - Michal Holubcik; Radovan Nosek; Katarína Sulovcova; Roman Weber (Communications - Scientific letters of the University of Zilina, 2015)
Combustion of biomass fuel itself as a renewable energy source does not automatically ensure the best use of its energy content with low emission production. Biomass combustion with bad settings of combustion conditions can be ineffective and with a high production of emissions. The article discusses the impact of various aspects on the power and emission parameters of the heat source. The influence of the amount of combustion air, the temperature of combustion air, the relative humidity of combustion air, the fuel feeding and fuel moisture on thermal power and emission production in automatic boiler for combustion of wood pellets were specifically verified. The results show that appropriate setting of these aspects has an effect on concentration of emissions from the combustion of biomass.